Current Situation of Solid Waste Management to Archive Sustainability in Klungkung Regency, Bali - Sapta Suhardono; Iva Yenis Septiariva; Wisnu Prayogo; I Wayan Koko Suryawan; Mega Mutiara Sari (Journal of Sustainable Infrastructure, 2023)
Most of the area in Klungkung Regency has a waste management system that needs to meet technical requirements regarding the compartment, sorting, collecting, transporting, and processing. Coverage of handling urban waste is still far from the target of 80% in 2019 (46% in 2013), and the amount of waste generation that is still recycled is still minimal (4.95 m3 in 2017). This research aims to make a master plan or strategy implemented to improve service coverage and the quality of solid waste management in the future. This research was conducted by conducting a direct survey and secondary data collection. The strategy adopted is to increase the utilization of waste infrastructure and facilities; increasing the capacity of solid waste facilities according to service targets; improving the quality of landfill management in the direction of sanitary landfills; developing regional final processing site management, and applying waste handling technology that is appropriate and environmentally friendly. The Millennium Development Goals (MDGs) contain the seriousness of improving sanitation conditions, which require increased public access to sanitation facilities in half of the population without access to sanitation. Increased population access to proper sanitation (domestic wastewater, solid waste and environmental drainage) to 100% at the level of basic needs.